Meditations on first philosophy in focus - Descartes, René, 1596-1650 (Routledge, 1993)
This includes the excellent translation by Haldane and Ross of Descartes' Meditations on First Philosophy, an introduction by Tweyman, and six articles indicating the diversity of scholarly opinion on method in Descartes' philosophy.
"Contains the excellent and popular Elizabeth S. Haldane and G.R.T. Ross translation."
Keywords: Descartes, René, -- 1596-1650 -- Et la méthodologie.; First philosophy.; Methodology.; Knowledge, Theory of.; Metaphysics; Methods; Métaphysique -- Ouvrages avant 1800.; Dieu -- Existence -- Preuve ontologique -- Ouvrages avant 1800.; Méthodologie.; Théorie de la connaissance.; Métaphysique.; metaphysics.; methodology.; epistemology.; PHILOSOPHY -- History & Surveys -- Modern.; First philosophy; Meditationes de prima philosophia (Descartes); Philosophy; France; Electronic books.; Early works